Evolusi Manajemen Keuangan dan Peran Sistem Informasi Akuntansi dalam Pengambilan Keputusan Perusahaan - Ignatius Oki Dewa Brata; Herry Achmad Buchory; Hasti Pramesti Kusnara; Rizky Ferari Oktavian; Yus Djunaedi Rusli; Dede Sugandi (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study examines the evolution of financial management theory and the role of Accounting Information Systems (AIS) in corporate decision-making through a descriptive-analytical literature review. Drawing on classical and contemporary academic sources from Scopus-indexed journals and reputable textbooks (1952–2025), the study traces the paradigm shift from administrative cash management toward strategic value creation and long-term sustainability. Six developmental eras are identified: traditional (pre-1950s), formal-quantitative (1950–1960s), capital market and capital structure (1970–1980s), asymmetric information and agency (1980–1990s), behavioral finance (1990–2000s), and digital-sustainable finance (2000–present). Findings show that each era progressively expanded the strategic role of AIS—from mere transaction recording toward decision-support, governance, ESG reporting, and AI-driven real-time analytics. The study contributes a conceptual framework linking financial theory evolution with AIS development, offering a foundation for future empirical research and modern financial management practice